2023
DOI: 10.3390/jcm12123997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Intensity and Psychosocial Burden of Acne Itch: Two Different Cohorts Study

Abstract: Background: Chronic itch is a common symptom of inflammatory skin diseases. This study was undertaken to evaluate the presence and intensity of itching in two different cohorts of acne subjects. Additionally, the influence of itching on the psychosocial status of acne individuals was assessed. Methods: Consecutive acne patients seeking dermatological advice and university students diagnosed with acne during dermatological screening were considered. The clinical and psychological aspects of acne were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Acne is not a life-threatening disease, but it definitely should not be considered a cosmetic problem due to the vast psychosocial burden. 5 , 6 Recently, our group has shown that acne patients, even those with mild acne, had decreased quality of life (QoL) and increased levels of stigmatization. 7 , 8 We also documented that in subjects with facial acne alexithymia, which is defined as the ability to identify and verbalize emotions, correlated both with QoL impairment and stigmatization level.…”
Section: Introductionmentioning
confidence: 99%
“…Acne is not a life-threatening disease, but it definitely should not be considered a cosmetic problem due to the vast psychosocial burden. 5 , 6 Recently, our group has shown that acne patients, even those with mild acne, had decreased quality of life (QoL) and increased levels of stigmatization. 7 , 8 We also documented that in subjects with facial acne alexithymia, which is defined as the ability to identify and verbalize emotions, correlated both with QoL impairment and stigmatization level.…”
Section: Introductionmentioning
confidence: 99%